A modified instantaneous reactive power algorithm for shunt compensation - Namrata Mishra; S. P. Gawande; Shailesh Deshmukh; K. T. Tan; Khalid Ansari; T. M. Yunus Khan; Naif Almakayeel; Wahaj Ahmad Khan (Scientific Reports)
Abstract Instantaneous Reactive Power (IRP p-q) Theory is well-thought-out as a benchmark for reference current generation in shunt compensation. The basic approach of this theory works optimally under balanced and sinusoidal source voltages. However, algorithm shows poor performance when source voltages are unbalanced (magnitude and phase) and non-sinusoidal. This paper proposes a new approach of IRP p-q theory for reference current generation in Distribution Static Compensator (DSTATCOM) in 3-ph, 4-wire distribution system with unbalanced, distorted source and non-linear loads, both. Algorithm is developed based on fundamental concept of equal current criteria to handle magnitude unbalance, improved formulations using time synchronization of source phase-a voltage for compensating phase unbalance, and fundamental positive sequence extraction to eliminate distortion in the source currents. This approach almost resolves most of misconceptions of instantaneous reactive power theory and provides better load compensation. Paper also presents the various downsides and misinterpretations of IRP theory and shows effectiveness of proposed approach (based on IRP p-q theory). Finally, detailed simulations and experimental results are provided to validate the effectiveness of proposed approach even under the different degree of supply voltages distortion.